Digital Resilience Among Individuals in School Education Settings: A Concept Analysis Based on a Scoping Review - Sun, Haiyan; Yuan, Changrong; Qian, Qian; He, Shuzhi; Luo, Qiong (Frontiers in Psychiatry, 2022)
Background: Nowadays, in an informational society, digital technologies are present in most areas of life, including school education fields. Students encountered risks or threats during online experiences. Digital resilience helps individuals recognize and manage the risks and threats they come across when they socialize, explore or work online, and plays an important role in the digital technology challenges. However, so far, the concept of digital resilience among individuals in the educational field has not been analyzed in detail. Objectives: The purpose of this study is to clarify the concept of digital resilience among students in a school education context, describe antecedents and consequences, and suggest a conceptual model for health educators. Methods: Walker and Avant’s concept analysis method was used to clarify the attributes, antecedents, and consequences from included articles. A thematic analysis approach of literature was utilized to describe the study findings. No date limitations were applied. Results: A total of 22 included articles provided data for digital resilience conceptualization. Five defining attributes for the concept were identified: (1) understanding online threats; (2) knowing solutions; (3) learning knowledge and skills; (4) recovering from stress; and (5) moving forward through self-efficacy. Antecedents included digital technology-related threats influenced by individual external and internal factors. Consequences were divided into two categories: behavioral performance and psychosocial functioning. Conclusion: Based on the results of the concept analysis, a preliminary conceptual model of digital resilience was described as a circular process towards greater performance and function in the form of understanding, knowing, learning, recovering and moving forward, when facing stressors, challenges or adversity. The conceptual model of digital resilience can be further tested and may inform the enhancement of digital-specific resilience measures and interventions for students.